2017
DOI: 10.1021/acsami.6b16411
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Single-Layer Coating of Gold Nanoparticles onto Multiple Substrates by Using an Intrinsically Disordered Protein of α-Synuclein for Nanoapplications

Abstract: Functional graffiti of nanoparticles onto target surface is an important issue in the development of nanodevices. A general strategy has been introduced here to decorate chemically diverse substrates with gold nanoparticles (AuNPs) in the form of a close-packed single layer by using an omni-adhesive protein of α-synuclein (αS) as conjugated with the particles. Since the adsorption was highly sensitive to pH, the amino acid sequence of αS exposed from the conjugates and its conformationally disordered state cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…The αS-MNPs were most extensively agglomerated, especially under the acidic conditions of pH 3.0 and pH 4.0 (Supporting Information, Figure S1C). As a matter of fact, this observation was consistent with our previous study preparing the αS-AuNP conjugates, in which αS was demonstrated to encapsulate AuNPs by exposing the acidic C-terminus . Considering an overall pI of 4.67 for the entire sequence of αS, the complete dispersion of αS-MNPs at pH 4.5 and their agglomerate formation under more acidic conditions indicate that the αS molecules localized on the MNP surface might expose its C-terminal acidic region by possibly forming a hydrophobic shield with the hydrophobic NAC region, which would separate the MNP surface-bound basic N-terminal region and the exposed acidic C-terminus (Supporting Information, Figure S1A).…”
Section: Results and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The αS-MNPs were most extensively agglomerated, especially under the acidic conditions of pH 3.0 and pH 4.0 (Supporting Information, Figure S1C). As a matter of fact, this observation was consistent with our previous study preparing the αS-AuNP conjugates, in which αS was demonstrated to encapsulate AuNPs by exposing the acidic C-terminus . Considering an overall pI of 4.67 for the entire sequence of αS, the complete dispersion of αS-MNPs at pH 4.5 and their agglomerate formation under more acidic conditions indicate that the αS molecules localized on the MNP surface might expose its C-terminal acidic region by possibly forming a hydrophobic shield with the hydrophobic NAC region, which would separate the MNP surface-bound basic N-terminal region and the exposed acidic C-terminus (Supporting Information, Figure S1A).…”
Section: Results and Discussionsupporting
confidence: 90%
“…As a matter of fact, this observation was consistent with our previous study preparing the αS-AuNP conjugates, in which αS was demonstrated to encapsulate AuNPs by exposing the acidic C-terminus. 45 Considering an overall pI of 4.67 for the entire sequence of αS, the complete dispersion of αS-MNPs at pH 4.5 and their agglomerate formation under more acidic conditions indicate that the αS molecules localized on the MNP surface might expose its Cterminal acidic region by possibly forming a hydrophobic shield with the hydrophobic NAC region, which would separate the MNP surface-bound basic N-terminal region and the exposed acidic C-terminus (Supporting Information, Figure S1A). As a matter of fact, the basic N-terminus bound to MNP was demonstrated to be blocked by the shield to trypsin digestion, whereas unbound αS was readily fragmented by trypsin (Supporting Information, Figure S1D,E).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natively unfolded nature of αS capable of exhibiting structural plasticity upon its self-assembly and multiple partner interactions would be responsible for the multitude of αS oligomers and thus multiple pathways of the fibrillation 9 . We have studied one particular type of meta-stable αS oligomers (Meta-αS-Os) since they act as a growing unit to exhibit the accelerated amyloid fibril formation in the presence of external stimuli such as shear force 10 , temperature change 11 , pH 12 , and organic solvents 13 which are suspected to alter the structure of Meta-αS-Os into a self-associative state. In fact, this unit-assembly process was confirmed by producing the pea-pod type gold nanoparticle (AuNP) chain aligned within the protein nanofibril of αS from the αS-encapsulated AuNP units (αS-AuNP) in the presence of the stimuli including hexane or pH change 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study by the same group was aimed at investigating the adhesion property of αS onto the surface of a few versatile substrates and a flexible flash memory utilizing αS–Au NPs as nano‐FG was explored. [ 134 ] These studies open up a new vista for utilizing programmable proteins as pluripotent components in bioelectronics.…”
Section: Protein‐based Transistor‐type Memorymentioning
confidence: 99%